Analisis Keterampilan Guru dalam Membuka dan Menutup Pelajaran pada Pembelajaran PAI di SDN 011 Sangatta Utara - Alawiyah Nabila; Muh Yusuf; Rizal Awaludin; Faelasup Faelasup (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research focuses on students who show less involvement and seriousness in learning. This research emphasizes the importance of using effective lesson opening and closing techniques during the learning process to increase student participation and achieve learning goals. This research aims to analyze the impact of teachers' skills in opening and closing PAI lessons on student engagement, using qualitative methods such as observation, interviews and document analysis to ensure the credibility of the data. teachers have used lesson opening and closing skills to increase student engagement, although not all of these skills are used optimally. There are several indicators, such as student interaction and use of tools, that are not commonly used by teachers. As a result, the skills for opening and closing PAI lessons have been implemented but not fully maximized by teachers. Despite this, students have shown a high level of engagement in learning, which indicates that the better the teacher's skills, the more engaged the students will be.